(untitled) (European Bison Conservation Newsletter, 2008)
Described is the status of European bison inhabiting Knyszyn´ska Forest, that is the largest forest complex situated close to Białowieża. The total area of forests available in the region for the bison is about 150 thousand ha. This population has a summer home range of about 10 thousand ha and the winter range of about 16 thousand ha. Bison numbers are estimated for 26 animals. Important for this population is an access to pastures, which became limited, due to afforestations and numerous beaver colonies. Damages to forest stands are estimated as negligible and highest annual compensations paid to farmers amounted to 50 thousand PLN. There were recorded several cases of poaching, and since 2005, few animals were designated for elimination.